2000
DOI: 10.1118/1.1328080
|View full text |Cite
|
Sign up to set email alerts
|

Inverse treatment planning for Gamma Knife radiosurgery

Abstract: An inverse treatment planning system for Gamma Knife radiosurgery has been developed using nonlinear programming techniques. The system optimizes the shot sizes, locations, and weights for Gamma Knife treatments. In the patient's prescription, the user can specify both the maximum number of shots of radiation and a minimum isodose line that must surround the entire treatment volume. After satisfying all of the constraints included in the prescription, the system maximizes the conformity of the dose distributio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 15 publications
0
15
0
Order By: Relevance
“…Source distribution in a hemispheric pattern results in ellipsoid concentric isodose clouds (model-dependent) which are optimally utilized by a shot-packing algorithm. In cases where dose to critical structures cannot be achieved by adjusting shot placement, weighting, and collimator size, the additional option of plugging one or more collimator channels allows for further customized shaping of each ellipsoid (25)(26)(27). This usually adds significant time to the treatment planning process as well as the treatment delivery time, as plugging is performed manually.…”
Section: Beamarrangementsmentioning
confidence: 99%
“…Source distribution in a hemispheric pattern results in ellipsoid concentric isodose clouds (model-dependent) which are optimally utilized by a shot-packing algorithm. In cases where dose to critical structures cannot be achieved by adjusting shot placement, weighting, and collimator size, the additional option of plugging one or more collimator channels allows for further customized shaping of each ellipsoid (25)(26)(27). This usually adds significant time to the treatment planning process as well as the treatment delivery time, as plugging is performed manually.…”
Section: Beamarrangementsmentioning
confidence: 99%
“…Besides the clinical LGP inverse treatment planning tool, multiple other studies have reported various techniques for inverse treatment planning optimizations (8)(9)(10). In light of these developments, the uniqueness of our current approach is its 2-step optimization process (ie preoptimize an open-shot plan first and then optimize individual sectors for an SBIM solution).…”
Section: Discussionmentioning
confidence: 99%
“…Yan et al 8 predetermined the shot number and used Powell's method to optimize the other parameters. However, Shepard et al 9 presented a different approach based on a nonlinear programming method to optimize all parameters simultaneously. In contrast, medial axis transform 1,10 of the lesion volume to a line skeleton has been exploited to direct shot placement, thereby creating a seed plan for subsequent optimization steps.…”
Section: Introductionmentioning
confidence: 99%
“…6 Stochastic combinatorial optimization has been widely used to solve it. 1,6,7,9 In these cases the shot packing problem would be overall, or partly, solved through a separate procedure prior to the optimization process. Thus, different portions of the optimization problem are fixed and the remaining variables are optimized using different algorithms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation